Geogebra-Assisted Animation Video Development and Artificial Intelligence for Critical Thinking Skills - Mustika Indah Baitul Susanti; Kashardi Kashardi; Masri Masri (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Learning mathematics in the 21st century requires developing critical thinking skills. However, traditional methods still dominate the classroom, such as using textbooks as learning resources and whiteboards as learning media, making it difficult for students to understand triangle congruence visually and dynamically. This research aims to develop animated video media using GeoGebra and Artificial Intelligence (AI) on triangle congruence material for grade IX junior high school students and to describe their validity and practicality. The research uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The test subjects were 14 grade IX students and 1 mathematics teacher, with validation sheet instruments and practicality questionnaires. The results showed that the average validity of the media was 90% with the very valid category, while the practicality reached 89.11% with the very practical category. These findings show that GeoGebra and AI-assisted animation videos are feasible alternatives to modern, interactive mathematics learning media that facilitate students’ critical thinking skills in triangle congruence materials.